Estudio jurídico-doctrinario de la vulneración de derechos de las víctimas del crimen de tortura y desaparición forzada en la justicia ecuatoriana - Tene Ordoñez, Juan Mateo (2023)
The present Work of Curricular Integration is titled: "Legal-doctrinary study of the violation of the rights of victims of the crime of torture and forced disappearance in Ecuadorian justice", it is essential to understand that when there are violations of human rights within a society there is a guarantee that people are under the protection, care of their rights, determining that when there are crimes of forced disappearance and torture, it produces a number of violations of human rights such as freedom, to have an identity, life dignity, health, physical integrity, among others, which is carried out with the aim of disappearing or torturing the victim, causing serious pain or suffering which can be physical or mental in nature, also subjecting them to conditions or methods that annul their personality or diminish their physical or mental capacity, for what purpose, would this crime be committed, for this reason, these two crimes are the most common within crimes against humanity, but with a point to be taken into account very important that it is the special subject that commits the crime, and that I have taken into account within my curricular integration project, its legal-doctrinary analysis is relevant with respect to which rights are violated, the development of these processes in national judicial instances and international, seeing it from a point that the majority of sentences against the Ecuadorian state is for the commission of crimes against humanity in the Inter-American Court of Human Rights, this legal-doctrinary study is carried out since they are violations of human rights , and that in most cases there has been no effective justice for the victims, then this leads to these processes being taken to international instances since the judicial instances in Ecuador have been exhausted and there has been no true justice, Therefore, it begins with the search for the truth and comprehensive reparation for the victims, being crimes against humanity violating rights such as life, human dignity, freedom, and physical and psychological integrity, all of this as objectives of the Law. International and universal jurisdiction, therefore said investigation focuses mainly on the analysis of these crimes, the procedure in judicial instances and their respective compliance with the sentences.